(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Research results of the XVII century construction, Hegumen House in Chernihiv, are presented. It is a historically significant local landmark. Attention was paid to historical data on foundation of the monastery and structure erection. The construction was built to serve as a refectory church of Peter and Paul. The purpose of the building was found to have been changed repeatedly during its existence. Constructional features of the structure remains were analyzed. Practical recommendations on its restoration were developed. Underground unit drawing was made, which is accessible to viewing. Detailed research was conducted. Reinforcements and brick wall construction, dated at a later period, were discovered. The wall construction brick was analyzed. Much attention was paid to durability and stableness of the underground unit.